Lessons Learned from the Implementation of Islamic Shari'ah Criminal Law in Aceh, Indonesia - Siregar, Hasnil Basri (Journal of law and religion, 2008)
In Indonesia, law reform is one of the important mandates of the national reform agenda, including the restructuring of various legal and political institutions at all levels of government, the regulatory implementation of the 1945 Constitution at the village level, and the ideological renewal necessary to make these changes real in Indonesian society. The policy direction of the People's Consultative Council (MPR) has changed from domination by the central authority toward freedom, autonomy and local government empowerment. Laws that were once imposed from the top now reflect power-sharing with local governments. In particular, the government has granted special (and virtually unlimited) autonomy to the province of Nangroe Aceh Darussalam (NAD, also known as Aceh). This article will explore how that autonomy has been influenced by a more robust adoption of Shari'ah law in Aceh.When the New Order rule fell on May 21, 1998, Indonesia moved from a centralized power to democratization, a process of legal development "from, by and for the people" through a decentralized system. The promulgation of Law 22 (1998) providing for local autonomy (which was amended in 2004 by Law 32) and Law 25 on the respective financial authority of the central and local governments is concrete evidence that decentralization is real in Indonesia.